Bad blood secrets and lies in a Silicon Valley Startup - Carreyrou, John. (New York Vintage Books, 2020)
"The full inside story of the breathtaking rise and shocking collapse of a multibillion-dollar startup, by the prize-winning journalist who first broke the story and pursued it to the end in the face of pressure and threats from the CEO and her lawyers. In 2014, Theranos founder and CEO Elizabeth Holmes was widely seen as the female Steve Jobs: a brilliant Stanford dropout whose startup "unicorn" promised to revolutionize the medical industry with a machine that would make blood tests significantly faster and easier. Backed by investors such as Larry Ellison and Tim Draper, Theranos sold shares in a fundraising round that valued the company at
Includes bibliographical references (pages 307-326) and index.
Keywords: Theranos (Firm)--History.